Highly ordered mesoporous silica film nanocomposites containing gold nanoparticles for the catalytic reduction of 4-nitrophenol - Jalani, MA; Yuliati, L; Lee, SL; Lintang, HO (Beilstein-Institut, 2024)
Indexed by WOS/SCOPUS/ERA